Drug-Related Homicide in Dade County (Miami), Florida; 1978-1980 - Quinn, James Francis (1986)
This study examines the characteristics of all homicide victims in Miami, Florida between 1978 and 1980 (N = 1186). Data was collected from the Medical Examiner's office and local law enforcement agencies. The study relates the distribution of various aspects of homicidal situations to one another and to behavioral, cultural, and structural groupings of victims. Special attention is given to levels of drug market involvement. Inferences are made at an aggregate level relevant to categories of victims. Social groupings of victims were better predictors of homicidal circumstances than socioeconomic status levels. SES was found to be most relevant to the ecological accessibility of crime scenes. Separation of drug-users from traffickers resulted in a drug-involvement variable with greater predictive utility than social grouping. Low SES persons killed in quarrels and the assassinations of drug traffickers were empirically linked to homicides in open areas. The deaths of traffickers appear to serve social control functions in this illicit market. The frequency of quarrels among low SES persons appears to reflect immediate activity to perceived deviance in stateless social settings. While traffickers' deaths tended to be highly visible to the public, those of low SES persons did not. The deaths of drug users were found to be less visible to the public than those of either traffickers or the non-drug involved. Both drug-involved groups tended to die in secluded locations, however. Analyses indicated that studies of urban homicide might benefit from a conceptualization of subculture that addressed cultural, structural, and behavioral influences. Such a multi-dimensional approach allows the various aspects of the homicidal act to be explored separately. This sort of approach is felt to be crucial in explaining the functions of violence within particular groups